Customizable process design for collaborative geographic analysis - Zaiyang Ma; Min Chen; Zhong Zheng; Songshan Yue; Zhiyi Zhu; Beichen Zhang; Jin Wang; Fengyuan Zhang; Yongning Wen; Guonian Lü (Taylor & Francis, 2022)
Collaborative geographic analysis can lead to better outcomes but requires complicated interactions among participants, support resources and analytic tools. A process expression with explicit structure and content can help coordinate and guide these interactions. For different geographic problems, the structure and content of collaborative geographic analysis are generally distinct. Since the process structure embodies the pathway of problem-solving and the process content contains the information flow and internal interactions, both the structure and the content of the process expression must be clarified during process customization. However, relevant studies concerning the collaborative geographic analysis process mainly focus on the process structure, which remains a “black box” in terms of the process content, especially the internal interactions. Therefore, this article designs a customizable process expression model that takes both process structure and content into account and proposes a corresponding process customization method for collaborative geographic analysis. Additionally, a support method for geographic analysis process implementation is also provided. To verify the feasibility and capability, these methods were implemented in a prototype system, and a case study on traffic noise assessment was conducted. The results suggest that the proposed strategy can effectively improve geographic analysis by customizing processes, guiding participants, performing interactions, and recording operations throughout the process.
Keywords: Biophysics; Genetics; Environmental Sciences not elsewhere classified; Biological Sciences not elsewhere classified; Information Systems not elsewhere classified